DAMPAK PERNIKAHAN DINI TERHADAP KESEHATAN REPRODUKSI: LITERATURE REVIEW - Nst, Aisyah Amalia; Dini, Aknes; Fasion, Arisah; Sunarsih, Tri; Rahmawati, Dechoni (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2023)
Marriage is a legally and religiously binding union between a woman and a man living together to start a family and continue offspring. Meanwhile, the problem of early marriage has not been resolved. This is quite a big problem for health workers, especially midwives. This literature review aims to analyze the impact of early marriage on reproductive health. Literature review based on problems, methods, similarities, and additional research ideas used in this research. 2 of the 4 studies we observed used qualitative research methods, 1 used qualitative and descriptive research methods, and 1 used descriptive research methods. The population used by the researchers was couples who married early and some of the results from the database obtained were from Google Scholar. The inclusion criteria for this research were informants who married at a young age and mothers who experienced problems as a result of marrying at an early age. Meanwhile, those excluded are women who marry at the right age and women who marry because of their desires. The results of this research show that the impact of early marriage is an immature reproductive system, and lack of maturity and early marriage is influenced by educational factors, economic factors, factors outside of marriage, and parental demands. Recommendations for further research where the impact of early marriage is a problem that must continue to be studied and solutions sought so that early marriage can be resolved.